2018
DOI: 10.21037/jtd.2018.04.04
|View full text |Cite
|
Sign up to set email alerts
|

The influence of heparin on coagulation function of patients undergoing video-assisted major thoracic surgery

Abstract: Background: Venous thromboembolism (VTE) remains a common complication after major thoracic surgery, especially resection of lung or esophagus cancer. This trial aims to explore the influence of preoperative usage of heparin on coagulation function of patients treated with video-assisted major thoracic Conclusions: All patients underwent video-assisted major thoracic surgery with preoperative use of heparin, there were significant differences in coagulation function after operation. However, mean values of all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…The intake of oral anticoagulation also influences the MELD score by raising the INR [ 18 20 ]. The deliberate or unintentional concealment of the intake of these drugs could lead to elevated MELD scores and the prioritization of those patients in the process of allocation.…”
Section: Discussionmentioning
confidence: 99%
“…The intake of oral anticoagulation also influences the MELD score by raising the INR [ 18 20 ]. The deliberate or unintentional concealment of the intake of these drugs could lead to elevated MELD scores and the prioritization of those patients in the process of allocation.…”
Section: Discussionmentioning
confidence: 99%
“…UFH was used in the studies of CADE, Kalweit, Tsutsumi, Mason, Deng, and Alai. 26,28,29,31,38,43 Prophylaxis with LMWH was performed in the studies of Daddi, Attaran, Song, Mantziari, Christensen, Song, Pannucci, and Esme. 30,33,35,36,40,41,42,44 Dentali, Agzarian, and Alai 37,47 compared prophylaxis of LMWH or heparin in patients receiving lung surgery; Tanaka 46 compared prophylaxis of an IPC or enoxaparin in patients who underwent esophagectomy for esophageal cancer;…”
Section: Discussionmentioning
confidence: 99%
“…In the studies of Daddi, Rollins, Agzarian, PARRY, Christensen, and Song, 30,34,37,39,40,41 prophylaxis with drugs was used starting before or after the operation to discharge. Deng, Alai, and Alai 38,43,47 declared a duration of prophylaxis from admission and continued until discharge.…”
Section: Discussionmentioning
confidence: 99%
“…Due to considering the risk of heparin related bleeding events, most thoracic surgeons chose to administrate anti-coagulant agents after surgery (2). Whereas, it was found the incidence of VTE was still existing from clinical practice, resulting in severe complications even death, which may be formed during or even before surgery, thoracic surgeons started to administrate anti-coagulants heparin sodium preoperatively to avoid VTE in most degree according to the need of actual clinical circumstance, the studies found there were no significant difference of coagulation function and bleeding volume between preoperative and postoperative administration of heparin (14,15). On basis of these outcomes and guidelines recommendation, we continued to further use LMWH preoperatively for providing lung cancer patients intended to receive video-assisted lobectomy with sufficient thromboprophylaxis.…”
Section: Introductionmentioning
confidence: 99%